Sejarah Perkembangan dan Peranan Radio Dalam Dakwah Islam - Erwan Efendi; Riki Armada Batubara; Akbar Ali Hamzah (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This research is to find out the history of the development and role of radio for Islamic da'wah broadcasts. The results of this research are radio is a mass media which has a role to convey news, information, knowledge and entertainment messages to the wider community, in 1878 Devid E Hughes was the first to send and receiving radio waves at that time he found that the balance of his induction caused interference with his telephone at that time radio was growing year by year in which radio was used as a medium to channel information, learning news especially in Islamic da'wah with the help of mass media the Islamic religion was more widespread and more knowledgeable about the religion of Islam with the help of the mass media of Islamic da'wah can be known to the wider community where the wider community can get to know their religion. Keywords: history of development, the role of radio